Lactoferrin-ginsenoside Rg3 complex ingredients: Study of interaction mechanism and preparation of oil-in-water emulsion. (30th November 2021) - Yan, Mi; Diao, Mengxue; Zhang, Chunhong; Shen, Xue; Zhan, Xin; Xi, Chunyu; Zhao, Changhui; Zhang, Tiehua
Highlights: Lactoferrin (LF) binds with 20(S)-ginsenoside Rg3 (Rg3) to form LF-Rg3 complex. Multi-spectroscopy and molecular simulation are used to reveal the interaction mechanism. The binding is mainly driven by hydrogen bonding and van der Walls force. LF-Rg3 emulsion is highly stable, showing promising potentials in foods and beverages. Abstract: Revealing the interaction mechanism between bovine lactoferrin (LF) and 20(S)-ginsenoside Rg3 (Rg3), thereby introducing Rg3 to LF and even into stable emulsions will contribute significantly to food valorization and food industry. Adding Rg3 to LF caused slight absorbance increment and static fluorescence quench of LF, implying the successful combination. Synchronous fluorescence, three-dimensional fluorescence and circular dichroism spectroscopy indicated the conformation changing of LF after binding with Rg3. Thermodynamic analysis showed that the binding happened spontaneously to form a LF-Rg3 complex with a molar ratio of 1:1, which was mainly driven by hydrogen bonding and van der Waals force. Molecular docking simulation provided extensive information about the optimized binding sites and the involved interactions. Finally, we prepared stable LF-Rg3 oil-in-water emulsion, showing great potential in foods and beverages. This work prepares all-natural functional ingredients, and also diversifies the effective food molecule-based delivery systems for LF and Rg3.